REKONSTRUKSI KONSEP PENDIDIKAN ISLAM YANG IDEAL DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MADRASAH - Hendrizal; Weli Sartika Sari; Rahmides Utami; Nofri Mayasril; Afri Rahmad; Della Nazda Putri; Rossy Gusman (STKIP Subang, 2024)
This research examines the reconstruction of the concept of ideal Islamic education in order to improve the quality of learning in madrasas. Islamic education plays an important role in shaping the character of students through the integration of Islamic values in the learning curriculum. The aim of this research is to describe the concept of ideal Islamic education, which includes reconstructing the curriculum, teaching methods, and increasing the competence of teaching staff to improve the quality of learning in madrasas. . This research uses the literature study method to collect and analyze secondary data from relevant sources related to Islamic education and the quality of learning in madrasas. The analysis was carried out in three stages: organizing, synthesizing, and identifying findings to build a comprehensive understanding regarding the reconstruction of the concept of ideal Islamic education. This research found that the reconstruction of Islamic education in madrasas through a holistic and integrative curriculum, developing teacher competency, and improving educational facilities can improve the quality of learning. The application of Islamic values, including the concepts of humanization, liberation and transcendence, as well as the integration of technology and collaboration with society, has proven effective in forming a superior generation. The challenges faced, such as quality gaps and minimal use of technology, require strategic solutions such as equal distribution of education funding and technology training to strengthen the relevance of the curriculum in facing global developments. This research implies the need for innovation in madrasa education by integrating technology and community collaboration, as well as increasing teacher capacity and facilities to achieve ideal Islamic education.